Narratives about Founding Cult Places and Forming Folkloric Biographies: Between Sacralization and Polemics - Djordjević Belić, Smiljana (Literatura Ludowa. Journal of Folklore and Popular Culture, 2025)
Cult places establishing motivated by an order/vow which a person receives in a dream or vision is an international motif, well known in Serbian folkloristic and literary tradition, too. This way of establishing cult places, accompanied by appropriate ritual practices, lives on even today in the territories of southern and southeastern Serbia. An individual who can establish contact with the otherworldly through dreams and visions often merits a special status in the community – some elements of their biography narratives are interpreted in such a way that they form sacralized biographies. The main motifs of such biographies have been singled out in this paper and their functioning in the collective is examined. Some sacralized biographies of the kind are well known today throughout Serbia, and they are also accepted by the official religion representatives, while others function only within the scope of a narrower community. It is shown that the process of sacralization depends on the time distance from the events under discussion, on the role of the community and individuals, but also on the mechanisms which are formed outside the framework of the local oral tradition, through the narratives of popular and media culture.